Dexamethasone 0.4mg Sustained-Release Intracanalicular Insert in the Management of Ocular Inflammation and Pain Following Ophthalmic Surgery: Design, Development and Place in Therapy - Brooks CC; Jabbehdari S; Gupta PK (Clinical Ophthalmology, 2020)
Cassandra C Brooks, 1 Sayena Jabbehdari, 1, 2 Preeya K Gupta 1 1Department of Ophthalmology, Duke University Eye Center, Durham, NC, USA; 2Department of Ophthalmology and Visual Sciences, University of Illinois at Chicago, Chicago, IL, USACorrespondence: Preeya K GuptaDepartment of Ophthalmology, Duke University Eye Center, 4709 Creekstone Drive, Suite 100, Durham, NC 27703, USATel +1 919 660-5234Fax +1 919 660-5070Email preeya.gupta@duke.eduAbstract: Inflammation and pain are two prevalent findings after ocular surgery. Corticosteroids are widely administrated as a core treatment to control post-surgical inflammation and pain. Improper patient adherence to post-operative eye drop regimens, limited bioavailability of topical eye drops, and the negative impact of preservatives used in many of these eye drops, has made a strong case for novel therapies in the treatment of post-operative pain and inflammation. This review of the literature will focus on the role of intracanalicular sustained-release dexamethasone (Dextenza, Ocular Therapeutix, Bedford, MA, USA) for the management of ocular inflammation and pain.Keywords: dexamethasone, sustained-release, intracanalicular, ocular inflammation, ocular pain, ophthalmic surgery